2018
DOI: 10.1108/er-06-2017-0131
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of work-life-balance (WLB) challenges on social sustainability

Abstract: Purpose The purpose of this paper is to examine the implications of work-life-balance (WLB) challenges for Nigerian female medical doctors. This study focusses on Nigeria, which its peculiar socio-cultural, institutional and professional realities constitute WLB as well as social sustainability (SS) challenge for female medical doctors. Design/methodology/approach Relying on qualitative, interpretivist approach and informed by institutional theory, this study explores how Nigeria’s institutional environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 78 publications
(139 reference statements)
5
70
0
1
Order By: Relevance
“…Decades ago, Hirschman (1970) reported the need to introduce changes in hospital work practices to correct this problem [119]. More recently, Mushfiqur et al (2018) emphasize the moral obligation to change matters related to the management of health institutions, including work hours and locations, the relationship with the environment, and, of course, better balance between personal life and professional life [120]. Increasing the flexibility of work schedules is one of the most common strategies to mitigate this problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decades ago, Hirschman (1970) reported the need to introduce changes in hospital work practices to correct this problem [119]. More recently, Mushfiqur et al (2018) emphasize the moral obligation to change matters related to the management of health institutions, including work hours and locations, the relationship with the environment, and, of course, better balance between personal life and professional life [120]. Increasing the flexibility of work schedules is one of the most common strategies to mitigate this problem.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the flexibility of work schedules is one of the most common strategies to mitigate this problem. Thus, the Medical Women's Federation (MWF) (2018) and Adisa et al (2017) promote part-time work as a way to effectively improve WLB and create a positive impact on both Social Security and the lives of workers [118][119][120][121].…”
Section: Discussionmentioning
confidence: 99%
“…Records show that Nigeria has the largest number of doctors in Africa (Adisa et al, 2017). However, Nigeria's political instability, economic downturn, and poor working conditions are causing many professionals, especially medical doctors, to migrate to 'greener pastures' with better career and WLB prospects (Mushfiqur et al, 2018). The Nigerian banking sector has also faced numerous challenges over the years.…”
Section: The Study Contextmentioning
confidence: 99%
“…WLB studies are largely concerned with the demands inherent in managing work and non-work-related activities (Lewis and Cooper, 2005) and the implications for organisations in enabling autonomy in terms of where, when, and how people achieve acceptable integration between both domains (Visser and Williams, 2006). However, while the concept in general is perceived as addressing an overall sense of harmony in the lives of working adults (Clark et al, 2004), its propositions often prioritise the experiences of working mothers, dual-income couples (Lewis and Humbert, 2010), and married workers with familial and home responsibilities (Mushfiqur et al, 2018) to the neglect of childless singles. Further, while significant research has been undertaken on WLB in Western developed nations (Wilkinson et al, 2017) and Asian countries (Rajadhyaksha, 2012), little is known about WLB challenges and experiences in an African context such as Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The first step of the DCE process is to identify and develop the attributes and corresponding levels. Based on reviews of the literature and government reports on the barriers and facilitators to motivating doctors who work in primary healthcare settings [2,4,9,10,[18][19][20][21][22][23][24][25][26][27][28], this study identified the nine following attributes that may influence doctors' working preferences within the MA: a) income, b) hospital location, c) working time, d) type of contract, e) training and career development, f) working environment, g) policy, h) benefits package, and i) workload. This list was then submitted to an expert panel comprised of doctors, researchers, and administrators for discussion.…”
Section: Attributes and Levelsmentioning
confidence: 99%